Signage Sebagai Elemen Desain Keamanan Taman pada Masa Pandemi Covid-19 berdasarkan Preferensi Wanita di Jaletreng Riverpark, Tangerang Selatan - Zain, Naily Syafira; Ristianti, Novia Sari (Jurusan Perencanaan Wilayah dan Kota, 2023)
People's behavior in public spaces has changed due to the Covid-19 Pandemic disruption. This disruption affects all levels of society but it is more concerning to women as a vulnerable group. Jaletreng Riverpark plays an important role as one of the city parks whose 70% of visitors are women. Unfortunately, the safety aspects has not been considered yet in Jaletreng Riverparks's existing design. There are still minimal signage designs available in this park, especially in terms of physical distancing. In fact, signage is a major matter that needs to be provided in order to form a safety design during pandemic. Therefore, it is important to know how to ensure safety design for women during the Covid-19 pandemic based on the signage aspect. The method used in this research is quantitative descriptive based on the women's preferences. The data collection technique was carried out by questionnaire. The findings show that every women are more likely to choose that is effective in providing distance but still supports sight view of the surrounding environment. They choose sticker sign for direct signage (63%) and partition/mural partition for indirect signage (61.6%).